Sequence alignment and phylogenetic analysis of Human Herpes Simplex Virus (HHV) using bioinformatics tool: a review. (6th August 2010) - Sohpal, Vipan Kumar; Dey, Apurba; Singh, Amarpal
Bioinformatics is the application of computational techniques to analyse the wet lab information associated with biomolecules on a commercial scale. Today's it concentrate on structural biology, genomics to gene expression studies. In this review we discuss the main principles that desirable bioinformatics analyses, sequence alignment and phylogenetic analysis from biological databases that are commonly used and examine some of the studies that are being conducted, particularly with reference to Human Herpes Simplex Virus (HHV). Finally provide an introduction and overview of the bioinformatics tools and software used for sequence alignment.